Efeito agudo e crônico do etanol sobre as enzimas NTPDase, 5'-nucleotidase, acetilcolinesterase, peroxidação lipídica e comportamento em ratos - Dias, Glaecir Roseni Mundstock (2004)
Ethanol is one of the most used substance in different societies. This study was performed in order to clarify the acute and chronic effects of ethanol on biochemical and behavioral parameters in male Wistar rats. The acute treatment consisted of oral administration by gavage of 0.8, 2.0, 4.0, 6.0 and 8.0 g ethanol/kg. All rats were sacrificed one hour and thirty minutes post treatment. The results showed that acute treatment induced a biphasic or hormetic effect in platelet NTPDase and 5'-nucleotidase activities. The activity of the enzyme acetylcholinesterase was inhibited in cerebral cortex, cerebellum, hypothalamus, hippocampus and striatum in 6.0g/kg and 8.0g/kg treated-groups. Moreover the acute treatment increased lipid peroxidation in the blood serum, liver, kidney and brain structures. The open-field and elevated plus-maze behavior was few altered by acute treatment. The chronic treatment consisted of oral administration of 20% ethanol solution during 31 weeks as only source of fluid. Rats were sacrificed 48 hours after the end of the treatment. The results showed reduction of the weight of treated group and initial hepatic injury in histological evaluation. There was a reduction in platelet NTPDase activity with ATP or ADP as substrate, while the 5'-nucleotidase activity was increased. The activity of the enzyme acetylcholinesterase was increased in cerebellum, hypothalamus, hippocampus and striatum. Lipid peroxidation was increased in the blood serum, liver and kidney. Besides we observed that interruption of the treatment for 48 hours elicited an anxiogenic effect in open-field and elevated plus-maze.